Creating an algorithm of a real-life situation as a form of mathematical modelling - Pyzara, Anna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
Algorithmisation is one of the forms of mathematical modelling. The necessity to create an algorithm imposes specific forms of work that brings numerous didactical benefits. The research presented here concerns math students' (future teachers) abilities which relate to mathematical modelling (i.e. creating algorithms) of an everyday situation. The analysis of their work demonstrated their lack of appropriate knowledge in the field of mathematical modelling – more than the half of the models did not work properly. The application of the form of the algorithm did not improve the quality of the models as well. However, it created an impulse to apply different tools (conditional instructions) and to apply the block diagram. The research shown points at weak sides of the students' skills, but on the other hand, it emphasizes the sense of joining modelling with creating algorithms.
Didactics of Mathematics, 2014, Nr 11 (15), s. 25-42
Keywords: mathematical modeling; algorithmisation; higher education